2001
DOI: 10.1207/s15327698jfc0102_03
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Adult Daughter Discussions of Caregiving Prior to Dependency: Exploring Conflicts Among European-American Women

Abstract: Thirty-six mother-adult daughter dyads discussed potential caregiving decisions prior to the mother's dependency. Their interactions were coded for exhibited conflict, use of control strategies, level of involvement in the discussion, and regard for each other. In addition, they reported their use of conflict strategies when having a disagreement with each other. Less than 40% of these dyads exhibited a disagreement. Mothers with high nonconfrontation scores were less involved in these discussions, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…These results are consistent with other research documenting social learning patterns within families (Kunkel, Hummert, & Dennis, 2006) and the development of communication patterns within families (Koerner & Fitzpatrick, 2002). To date, the majority of research on family communication patterns has examined two generations in families with young children or adolescents (Koerner & Fitzpatrick, 2002), but interest is developing in extending study to older families (e.g., Fingerman, 2003;Pecchioni & Nussbaum, 2001) and to three generations (Miller-Day, 2004).…”
Section: Intergenerational Transfer and Understandingsupporting
confidence: 88%
“…These results are consistent with other research documenting social learning patterns within families (Kunkel, Hummert, & Dennis, 2006) and the development of communication patterns within families (Koerner & Fitzpatrick, 2002). To date, the majority of research on family communication patterns has examined two generations in families with young children or adolescents (Koerner & Fitzpatrick, 2002), but interest is developing in extending study to older families (e.g., Fingerman, 2003;Pecchioni & Nussbaum, 2001) and to three generations (Miller-Day, 2004).…”
Section: Intergenerational Transfer and Understandingsupporting
confidence: 88%
“…Research has shown that support exchanges within mother–daughter and mother–son dyads take on distinct patterns. Much work has explored the intensive support provision of middle-aged daughters who provide care for their aging mothers suffering from chronic illness (Horowitz, 1985; Pecchioni & Nussbaum, 2001; Pillemer & Suitor, 2014; Ward-Griffin, Oudshoorn, Clark, & Bol, 2007). However, much work often focuses exclusively on the problems of the individual receiving support (e.g., the health problems of an aging mother receiving caregiving from her daughter) and not the perceptions of the individual giving support.…”
Section: Mother–child Support Exchangesmentioning
confidence: 99%
“…5.1), for instance, only one (Gottman, Levenson, & Woodin, 2001) even mentions Darwinian principles and none uses TNS (or any other theories of evolution) as a basis for formulating hypotheses or research questions. This is true even of studies on topics about which TNS would have clear and testable implications, such as jealousy (e.g., Aune & Comstock, 2002) or parent-child conflict (e.g., Pecchioni & Nussbaum, 2001). TNS does not fare much better in family communication textbooks.…”
Section: (Why Aren't We) Using Tns In Family Communication Researchmentioning
confidence: 99%